Hi DSP experts,

Can someone please explain to me why it makes sense to calculate group delay using the second equation below. It is under “help grpdelay”

Theory: group delay, g(w) = -d/dw [arg{H(e^jw)}], is the rate of

change of phase with respect to frequency. It can be computed as:

d/dw H(e^-jw)

g(w) = -------------

H(e^-jw)

Also, I could not figure out why d/dw B(e^-jw) = sum(k b_k e^-jwk)

Is a “-j” missing?

Note that,

d/dw B(e^-jw) = sum(k b_k e^-jwk)

d/dw A(e^-jw) = sum(k a_k e^-jwk)

Thanks,

Ntsanderh C. Azenui, PhD